Is there a southern-sclerosis? Worker reallocation and regional unemployment in Italy - Chiara Mussida; Francesco Pastore (Institute for the Study of Labor (IZA), 2012)
Theoretical reasoning justifies different signs of the relationship between the local variation in unemployment rates and the extent of workers reallocation. This paper aims to test different theoretical hypotheses in the case of Italy by using the longitudinal files of the Italian labour force survey over the years from 2004 to 2010. We find that labour turnover, as well as inflows and outflows separately, differ significantly at the regional level and are ceteris paribus positively related to the unemployment rate. In addition, we study the determinants of labour turnover across NUTS1 and NUTS2 geographical units and find that it correlates positively with structural change, as measured by the Lilien index, and negatively with the degree of industrial concentration, as measured by the Herfindahl index. Once we control for sectoral shifts and industrial concentration, we note a reduction of between 25 and 40% of the regional gap in labour turnover rates. This general conclusion is robust to the use of different control variables.
Keywords: C33; J63; P25; P52; R23; 330; regional unemployment; labour turnover; labour reallocation; structural change; Regionale Arbeitslosigkeit; Arbeitsmobilität; Regionaler Strukturwandel; Italien